2013
DOI: 10.1007/s00586-013-2714-8
|View full text |Cite
|
Sign up to set email alerts
|

A needle micro-osmometer for determination of glycosaminoglycan concentration in excised nucleus pulposus tissue

Abstract: Purpose Aggrecan is one of the major macromolecular components of the intervertebral disc (IVD) and its loss is an early sign of degeneration. Restoration of aggrecan, and hence of biomechanical properties, is a major objective of biological therapies. At present, assessment of aggrecan concentration via its glycosaminoglycan (GAG) content is accomplished using biochemical and histological methods which require sacrifice of tissue. A minimally invasive method for assessing GAG, and hence aggrecan, which can av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The accumulation of Lac and a decrease in pH may be the initiating factor in disc degeneration and discogenic back pain (). MRI methods to measure pH in IVD would therefore be valuable in research and clinical settings.…”
mentioning
confidence: 99%
“…The accumulation of Lac and a decrease in pH may be the initiating factor in disc degeneration and discogenic back pain (). MRI methods to measure pH in IVD would therefore be valuable in research and clinical settings.…”
mentioning
confidence: 99%
“…Zuo et al, demonstrated with magnetic resonance spectroscopy that elevated water/proteoglycan ratio correlated with symptomatic patients versus controls, and with positive discography versus negative discography [ 22 ]. In addition, mechanical microsensors [ 23 ], fiber optics microsensors [ 24 ], and proteoglycan osmodetectors [ 25 ] were employed to detect minute pressure or osmolarity changes in the IVD. However, these and other new advances have not been fully validated in a controlled clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The other core hypothesis to simulate degeneration was the modification of the tissues’ permeability, but this mechanism is highly dependent on the degeneration grade. Mild degeneration, as reported by Detiger et al ( 2013 ), stands for grades III–IV on Thompson’s scale (Thompson et al, 1990 ; Sivan et al, 2013 ). Low to mild degeneration are probably related to a decrease of CEP permeability, due to the calcification of this component, while mild to severe degeneration are more likely associated with an increase of CEP permeability, as a result of probable crack openings (Urban, 2000 ; Adams and Dolan, 2012 ; Stefanakis et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%